Pengaruh Self Efficacy, Pengetahuan Pajak dan Motivasi Karir Terhadap Minat Mahasiswa untuk Berkarir di Bidang Pajak - Nada Salsabila; David Pangaribuan; Triana Yuniati (Politeknik Kampar, 2024)
The aim of this research is to test and analyze the influence of self-efficacy, tax knowledge and career motivation on students' interest in pursuing a career in the tax field. This research method uses quantitative research methods, with the type and source of data, namely primary data obtained from the results of questionnaires. The population and sample for this research are accounting students from the Class of 2020, 2021 and 2022 who are taking a concentration in taxation and students who have taken taxation courses. The sampling technique used was purposive sampling and produced 100 samples of processed data that met the criteria. The analytical method used is classical assumption testing, regression testing, hypothesis testing. The results of this research show that self-efficacy has no influence on students' interest in pursuing a career in tax, tax knowledge influences students' interest in pursuing a career in tax and career motivation influences students' interest in pursuing a career in tax.